تحضير وتشخيص قاعدة شف مشتقة من( 1,8 ثنائي أمينو - نفثالين )وبعض معقداتها ودراسة فعاليتهما البايلوجية - علي, بان خليل (University of Thi-Qar Journal of Science, 2014)
A Schiff baseligand N-(2-hydroxy-3-methoxy-N-[(1Z)-phenenylmethylene] naphthalene-1,8-diamin and its seven complexes have been synthesized and characterization on the bases of elemental analysis,IR, NMR ,Mass spectra , Conductance measurements .Spectroscopy and other analytical studies that the complexes of Cu(II),Zn(II),Ni(II) and Fe(II) are square planer while Co(II),Cr(III) and Ti(III) are octahedral.The and equivalency of (L1,L2)complexes have been studied in two methods Mole-Ratio and Continuous Variation (Job method) , and accordance of these complexes with Beer,s Law have also studied the study ends with Antibacterial screening tests were also pre formed agnist bacteria,The study values  indicate that the metal complexes and the schiff base exhibit antibacterial activity.